PULMONARY INVOLVEMENT IN RHEUMATOID ARTHRITIS - D. V. Bestaev; D. E. Karateev; E. L. Nasonov (Научно-практическая ревматология)
Rheumatoid arthritis (RA) is an autoimmune disease with erosive and destructive polyarthritis and systemic manifestations. Pulmonary involvement (PI) is common in RA. With high-resolution computed tomography, the detection rate of PI in RA is as high as 50%. PI is a direct cause of death in 10–20% of patients with RA. Autoimmune mechanisms play a leading part in the development of PI in RA. Under the hypothesis advanced by M. Selman et al., that impaired alveolocyte regeneration processes after injury rather inflammation underlie the pathogenesis of pulmonary fibrosis. The pathological process is triggered by damaged alveolocytes and characterized by the migration and proliferation of fibroblasts and myofibroblasts, the suppressed apoptosis of the latter, and the enhanced activity of pneumofibrosis-stimulating cytokines. This gives rise to remodeling of the extracellular matrix, including destruction of the basement membrane, angiogenesis, and fibrosis. The paper considers the types of lung injury in RA and main methods for diagnosis and therapy.